1988
DOI: 10.1126/science.2838906
|View full text |Cite
|
Sign up to set email alerts
|

Poliovirus Host Range Is Determined by a Short Amino Acid Sequence in Neutralization Antigenic Site I

Abstract: The mouse-adapted strain of poliovirus type 2 (Lansing) induces fatal poliomyelitis in mice after intracerebral inoculation, whereas mice inoculated with poliovirus type 1 (Mahoney) show no signs of disease. Previous work indicated that the adaptation to mouse virulence is associated with the viral capsid proteins and that mutations in neutralization antigenic site I of poliovirus reduce neurovirulence of the Lansing strain in mice. The role of antigenic site I in mouse neurovirulence was further explored by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
98
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(99 citation statements)
references
References 22 publications
1
98
0
Order By: Relevance
“…Similar mutations have been associated with mouse adaptation (32,45), ability to use mutated receptors (9), and ability to persist in neuroblastoma cells (11) in different Mahoney variants.…”
Section: Discussionmentioning
confidence: 99%
“…Similar mutations have been associated with mouse adaptation (32,45), ability to use mutated receptors (9), and ability to persist in neuroblastoma cells (11) in different Mahoney variants.…”
Section: Discussionmentioning
confidence: 99%
“…Chimeras in which the main loop of site 1 of the mouse-adapted Lansing strain of type 2 poliovirus was inserted into the equivalent site of the type 1 strain Mahoney have been reported and render the virus able to replicate in mice (Murray et al, 1988b;Martin et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Antigenic variants of PV2/Lansing with altered neurovirulence display amino acid changes of VP1 residues 93 to 105, with five out of 14 having changes at position 99 (La Monica et al, 1987b). Insertion of an oligonucleotide cartridge corresponding to amino acids 95 to 102 of PV2/ Lansing into the identical site in PV1/Mahoney (avirulent for mice) resulted in a virus which induced paralytic disease in mice (Martin et al, 1988;Murray et al, 1988). These studies suggest that changes in neutralization site 1 may alter receptor binding and consequently the pathogenicity of the virus for mice.…”
Section: Discussionmentioning
confidence: 87%
“…PV2/W-2 and PV2/Lansing are the only mouse-adapted poliovirus strains that have been well characterized biologically and, in addition, PV2/Lansing has been cloned and sequenced (Racaniello, 1984;La Monica et al, 1986). Recombination studies have revealed that the PV2/ Lansing capsid region is necessary for mouse intracerebral neurovirulence when compared with the nonmouse-adapted PV1/Mahoney strain (La Monica et al, 1986;Martin et al, 1988;Murray et al, 1988). Rather than using host range to analyse the molecular basis for virulence and attenuation, our general strategy is to compare the two mouse-adapted PV2 strains, Lansing and W-2.…”
Section: Introductionmentioning
confidence: 99%